2009
DOI: 10.1007/s00198-009-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

The differences of femoral neck geometric parameters: effects of age, gender and race

Abstract: Summary This study aims at investigating the effects of age, sex, and ethnicity on five femoral neck geometric parameters (FNGPs): femoral neck periosteal diameter, cross-sectional area, cortical thickness, sectional modulus, and buckling ratio and found that the three factors would influence the FNGPs. Introduction Bone geometry is one of the most important predictors of bone strength and osteoporotic fractures. This study aims at investigating the effects of age, sex, and ethnicity on five femoral neck geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…The more rapid expansion in white compared to Japanese women appears to preserve the section modulus. However, few studies exist to provide reference databases of hip geometric parameters for Chinese men and women [14][15][16]. We have previously reported on changes of hip axis length (HAL) in Chinese men and women and found no association with HAL or femoral neck fracture [14].…”
Section: Introductionmentioning
confidence: 99%
“…The more rapid expansion in white compared to Japanese women appears to preserve the section modulus. However, few studies exist to provide reference databases of hip geometric parameters for Chinese men and women [14][15][16]. We have previously reported on changes of hip axis length (HAL) in Chinese men and women and found no association with HAL or femoral neck fracture [14].…”
Section: Introductionmentioning
confidence: 99%
“…Bone atlas and CT scan data suggests that women have larger canals, relatively shorter necks, more varus necks, greater anteversion [2,3,4], less acetabular abduction and more acetabular anteversion [5]. As a result, it has been suggested that a gender specific implant is needed to adequately address such gender-related anatomical variations when considering cementless femoral stems in THA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in femoral anatomy [1,2,3,4] and acetabular anatomy [5] have been partially ascribed to gender differences. Traditionally, femoral stems for THA have been designed across an entire population including both males and females.…”
Section: Introductionmentioning
confidence: 99%
“…FN periosteal expansion with ageing has been reported in Chinese men and women [102][103][104][105]. From direct or indirect comparisons of these cross-sectional studies, agerelated periosteal apposition seems to be less in Chinese than Caucasian men but similar or greater in Chinese than Caucasian women.…”
Section: Appendicular Skeletonmentioning
confidence: 94%
“…From direct or indirect comparisons of these cross-sectional studies, agerelated periosteal apposition seems to be less in Chinese than Caucasian men but similar or greater in Chinese than Caucasian women. For instance, FN periosteal expansion was reported as 0.5-0.6% per decade in Chinese men, compared with about 0.8-1.0% per decade in Caucasian men [102,104,106]. In 829 healthy Chinese and 1,181 healthy Caucasian women and men aged 18-93 years, hip structure analysis suggests periosteal apposition and endosteal resorption were both less in Chinese than Caucasian men, while they were similar in Chinese and Caucasian women [105] (Fig.…”
Section: Appendicular Skeletonmentioning
confidence: 96%